ESTIMATION OF EFFICACY OF ANTIPARASITIC DRUG AVERTEL AGAINST ENDO- AND ECTOPARASITES IN DOGS AND CATS - V. B. YASTREB; T. S. NOVIK (Российский паразитологический журнал, 2016)
Efficacy of injection form of the combined drug Avertel applied against helminthosis and arachno-entomosis in dogs and cats is studied. Investigations were carried out on dogs and cats spontaneously and experimentally infected by cestodes and nematodes, ticks Sarcoptes scabiei, Otodectes cynotis, Notoedres cati, fleas Ctenocephalides felis, lice Linognathus setosus, biting louses Trichodectes canis. Avertel was applied to the animal's skin surface in the forearm and shoulder joint singly at helminthosis, twice at arachno-entomosis at a dose of 1 ml/kg or 0,5 mg/kg of aversectine C1 and 5 mg/kg of praziquantel per kg. Singly applied to the skin in the tested dose Avertel shown a 100 % efficacy against cestodes in dogs and cats. Efficacy of this drug against nematodes in cats was 100 %, in dogs – 96,9 %. Applied twice to the skin with the interval of 14 days Avertel shown a 100 % efficacy against otodectosis in dogs and cats, sarcoptosis in dogs, notoedrosis in cats, linognatosis and trichodectosis in dogs. At ctenocephalosis in dogs the efficacy was 83,3, in cats – 87,5 %. The preparation was well tolerated by animals, no side effects were observed.